2018
DOI: 10.3389/fpsyt.2018.00632
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Multimodal Neuroimaging Study to Examine Relationships Between Resting State Glutamate and Task Related BOLD Response in Schizophrenia

Abstract: Previous studies have observed impairments in both brain function and neurometabolite levels in schizophrenia. In this study, we investigated the relationship between brain activity and neurochemistry in off-medication patients with schizophrenia and if this relationship is altered following antipsychotic medication by combining proton magnetic resonance spectroscopy (1H-MRS) with functional magnetic resonance imaging (fMRI). We used single voxel MRS acquired in the bilateral dorsal anterior cingulate cortex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 75 publications
6
30
0
Order By: Relevance
“…Decreased prefrontal activation (hypofrontality) has been reported in other neuroimaging reviews of chronic patients and is linked with negative symptoms and antipsychotic response [40]. In a recent study [41] of the relationship between BOLD signals and glutamate levels in the salience network (SN) and the default mode network (DMN) during resting-state scans in a sample of schizophrenia patients, the authors found a positive correlation between glutamate levels and activation in the HC group and in the SZ medicated group (positive but decreased at baseline), but a negative relationship in the SZ non-medicated groups. After 6 weeks, all the SZ patients were receiving antipsychotic treatment, and they all showed a positive correlation between glutamate levels and BOLD signals, but with significantly lower activation compared to the HC group in the SN (ACC and bilateral insula) and DMN (precuneus).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased prefrontal activation (hypofrontality) has been reported in other neuroimaging reviews of chronic patients and is linked with negative symptoms and antipsychotic response [40]. In a recent study [41] of the relationship between BOLD signals and glutamate levels in the salience network (SN) and the default mode network (DMN) during resting-state scans in a sample of schizophrenia patients, the authors found a positive correlation between glutamate levels and activation in the HC group and in the SZ medicated group (positive but decreased at baseline), but a negative relationship in the SZ non-medicated groups. After 6 weeks, all the SZ patients were receiving antipsychotic treatment, and they all showed a positive correlation between glutamate levels and BOLD signals, but with significantly lower activation compared to the HC group in the SN (ACC and bilateral insula) and DMN (precuneus).…”
Section: Discussionmentioning
confidence: 99%
“…However, so far there is not a systematic study of the physiological and pathological effects on neurometabolic changes, especially during young adulthood (and late adolescence) when most patients experience FEP. The fact that only a few longitudinal MRS studies of FEP have been published (15,17,(19)(20)(21)(22)(23), especially none to date performed at 7T, limits current progress in studying neurometabolic changes in early stages of psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The combined proton MRS and fMRI study are particularly useful for short-term longitudinal studies on the effects of medication, which is invariant to brain structural change. In this study [202] , the relationship between Glx/Cr levels and BOLD response significantly changed after six weeks of medication for schizophrenia patients, although factors that confound interpretations of the results remain. More examples of multimodal imaging studies on schizophrenia are given in recent review articles [203, 204] .…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 65%
“…A concerted use of three MRI modalities, namely, resting-state of fMRI, structural MRI, and diffusion MRI, was able to simultaneously reveal abnormalities from these three kinds of MRI images and, thereby, identify the cortico-striato-thalamic circuits that might be related the cognitive impairments in schizophrenia [201] . In addition to the multimodal imaging investigation of structural and functional brain abnormalities in schizophrenia, proton MRS has also been used in combination with fMRI to investigate cognitive impairment in schizophrenia at both neurometabolic and functional levels [202] . The combined proton MRS and fMRI study are particularly useful for short-term longitudinal studies on the effects of medication, which is invariant to brain structural change.…”
Section: Multimodal Imaging Data Fusion: Diseasesmentioning
confidence: 99%